Play—An essential part of children’s lives and their computational empowerment - Tikkanen, Ruut; Iivari, Netta; Paananen, Pirkko (Frontiers in Education, 2023)
Play – an essential part of children’s life and their computational empowerment This article addresses the computational empowerment of children, with an emphasis on the importance of play in realizing it. Although play has been brought up as central for children within numerous disciplines, there is a lack of thorough treatment of the phenomenon in the context of technology design, computational thinking, and computational empowerment. The objective of this research is to open the eyes of adults to see children’s play and improvisation as not only an essential part of children’s life but also an important part of their computational empowerment. We organized numerous participatory design sessions with children (aged 5–6 years), during which play was supported to obtain material for designing a music game. Our analysis of the sessions showed that play had numerous important functions in the design sessions with the children. We recommend that researchers offer various forms of play and improvisation for children during design sessions to support children’s creativity, narratives, embodiment, and, ultimately, their computational empowerment. Keywords: Children, play, participatory design, education, computational thinking, computational empowerment